Anaerobic treatment of a paper plant effluent - Russo, Stephen Leonard (Department of Chemical Engineering, 2016)
The objective of this study was to investigate the anaerobic biological treatment of an organic-bearing wastewater from a particular paper manufacturing process at laboratory scale. The process produces paper by re-pulping waste paper. Effluent from the process has a Chemical Oxygen Demand (COD) concentration of approximately 4500 mg/l with a sulphate content of approximately 300 mg SO₄²⁻/l. The upflow anaerobic sludge bed (UASB) reactor was selected for the study. Important information derived from the laboratory treatability study was: (l) the extent of COD removal possible; (2) the effluent quality; (3) the maximum COD leading rate (kgCOD/m³ reactor/day) which can be achieved while maintaining reasonable COD removal, and the influence on loading rate of temperature: (4) the nature of the sludge produced in the reactor with particular reference to the extent of pelletisation: and (5) the effect of reactor effluent recycling on alkalinity requirements.